Comparison and evaluation of the efficacy of topical drug formulations containing diclofenac - Bodnár, Krisztina; Kis, Gergő; Józsa, Liza (De Remediis, 2026)
The choice of dermal dosage form is critical for therapeutic success, as it directly influences drug absorption, bioavailability, and overall efficacy. The skin possesses distinct physiological and anatomical characteristics that determine the performance of topical formulations. In addition to efficacy, the selected dosage form affects patient comfort, treatment adherence, and overall therapeutic outcomes. Therefore, optimizing dermal formulations is essential. This study aimed to compare different diclofenac sodium-containing dermal dosage forms in terms of drug release, bioavailability, cytotoxicity, and anti-inflammatory activity. Three formulations were evaluated: cream, foam and gel. Texture analysis was performed to predict bioavailability. Drug release and membrane penetration were assessed using a Franz diffusion cell combined with UV–VIS spectrophotometry. Biocompatibility was determined by MTT assay on HaCaT human keratinocyte cells. The in vitro anti-inflammatory effect was evaluated by measuring TNF-α and IL-1β levels using ELISA. Franz diffusion studies demonstrated that the foam formulation exhibited the most favorable penetration profile, followed by the cream and gel. MTT results confirmed acceptable biocompatibility for all formulations; however, cream and gel showed a greater reduction in cell viability, likely due to excipients. The foam achieved the greatest reduction in inflammatory markers, while no significant difference was observed between cream and gel. Based on the results, it can be concluded that the foam formulation containing diclofenac sodium is the most advantageous in terms of drug release, bioavailability, toxicity, and anti-inflammatory effect.